"General Frost": A Nature-Based Solution and Adventure Tourism: A Case Study of Snowshoeing in Siberia. (March 2022) - Jirásek, Ivo; Hanuš, Miroslav
Adventure tourism activities are deeply connected with risk situations. Therefore, adequate risk management has to be a necessary part of this segment of tourism. A nature-based solution is seen as a very effective approach here. Using the form of an autoethnographic case study and feedback from participants' interviews and mind maps, the article discusses the possibilities that snowshoeing and winter camping provide. This developing sport, recreation, and tourism should be classified as adventure tourism (mode of experiencing) and nature based tourism (traveling to natural environment). Climatic conditions, particularly severe frost, during the 2-week journey in Siberia greatly affected the choices and risk management of the group. Changes in the originally planned route according to weather conditions and possible reduction of risk may become examples of a NBS.